A new language for electromagnetic knowledge specification - Hoole, S.R.H.; Mascrenghe, A.; Navukkarasu, K. (Elsevier B.V., 2007)
Knowledge specification languages are used in the design of electromagnetic and other products. But these, traditionally used to represent knowledge, do not exploit the full features of object-oriented programming and lack back-tracking. This paper provides the description of the prototype of a new knowledge specification language that we developed, to overcome these short-comings. The specific focus is on electromagnetic product design, vis-à-vis the selection of motors from user specifications. We show that a full integration of object-oriented programming and logic programming is possible.
Keywords: Finite element analysis; Interpreter; Knowledge specification language; Motor design; Optimisation